Systems medicine for multiple myeloma: a review on decision support systems - Ganzinger, Matthias; Haux, Christian; Karmen, Christian; Wetter, Thomas; Knaup-Gregori, Petra (MEDINFO 2015, 2015)
Systems medicine is a current approach trying to improve treatment for patients with complex diseases by analyzing as much phenotype and genotype data as possible for the disease in question. For individualized treatment decisions in clinical practice, this task has to be supported by an application system with decision support component. For a research project on systems medicine we reviewed methods for decision support. Criteria for selecting a method are derived from characteristics of the data and the diseases. They include, among others: dimensionality of data and existence of a priori models for diseases. As a result we decided to implement a prototype system with a case-based reasoning component for systems medicine on multiple myeloma.